If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 2b + 4a + b = 0 Reorder the terms: 3a + 4a + 2b + b = 0 Combine like terms: 3a + 4a = 7a 7a + 2b + b = 0 Combine like terms: 2b + b = 3b 7a + 3b = 0 Solving 7a + 3b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. 7a + 3b + -3b = 0 + -3b Combine like terms: 3b + -3b = 0 7a + 0 = 0 + -3b 7a = 0 + -3b Remove the zero: 7a = -3b Divide each side by '7'. a = -0.4285714286b Simplifying a = -0.4285714286b
| 95-7x=29x+19 | | 10-6c=-5c-2 | | 5-6s=-7 | | 3x+12x=10-8x | | 78-5x=10x+28 | | 3-4u=-17 | | 107-7x=38x+22 | | x=x^3 | | -4x-3=21 | | 2x+3y+4x+5y= | | 7-8x=57-22x | | 6+8x=27+x | | -5x+1=21 | | 65-5x=4x+22 | | 8m+8n= | | 5x*2+11=0 | | -5+1=21 | | 5x-3=15x-113 | | 14-9x=109-44x | | 6x+32=13x-45 | | 10x-4=-4 | | 5x+14=-56-9x | | 6x+10=106-6x | | 152-6x=5x+9 | | 6y+7h-2y+3h= | | -34-2x=8-8x | | 87-4x=3x+10 | | x^2+x+.75=0 | | 3(x-7)=19-x | | 4x+13=113-6x | | 1x+13=113-6x | | 3x^3-3x^2+x-1=0 |